Students’ Performance in Arranging English Words into Simple Sentences Utilizing Jumbled-Word Cards - Juhansar; Prasetyoaji, Ari; Pabbajah, Mustaqim; Mahardika, Nia Arba (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2022)
In the modern era, teachers can use jumbled words as a medium in the learning-teaching process, especially in English. This research aims to discover the students' performance in arranging simple sentences utilizing jumbled-word cards. This research relays on quantitative descriptive research. The respondents of this research are the eight-grade students of MTs Al Kautsar Sleman in the academic year 2021/2022. The researchers select one class as the respondents, consisting of 15 (fifteen) students. The students were taught by applying a jumbled-words technique. The instrument for collecting data was a test. After collecting data, the researchers analyzed students’ performance by measuring the grammatical aspect of the test results. The test is about simple present tense and present continuous tense. This research shows that 10 (ten) students’ have 8 (eight) scores and 5 (five) students have 7 (seven) scores. Both are categorized in the "good" performance category. The mean average score for the student's performance in arranging jumbled words into simple sentences 7,6 is categorized as "good" performance. This research shows that students could understand most items in Subject + Verb. It is proven by the performance score percentage of 35% or 592 points. Meanwhile, the lowest true work in arranging the word is on the use of subject + verb + object + adjective/adverb with 32% or 552 points.